2002
DOI: 10.1002/macp.200290023
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of a Poly(ethylene terephthalate) Surface by the Selective Alkylation of Acid Salts

Abstract: Chemical modification of the hydrophilic surface of poly(ethylene terephthalate) (PET) was examined by the selective alkylation of the acid salt on the surface using acyl bromides as an electrophile with catalytic potassium fluoride. The hydrophobicity of the PET surface increased as the alkylation reaction of the hydrolyzed surface proceeded. The chemical incorporation of the alkylation reagents was confirmed by the presence of fluorine peaks in X‐ray photoelectron spectroscopy (XPS) from the fluorinated reag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…). After KOH hydrolysis, the contact angle of PET surface decreases from 85° to 75°, consistent with previous literature . Then the KOH‐treated PET samples were immobilized with styrene using the following conditions: a monomer‐to‐initiator molar ratio of 466, temperature of 100 °C and reaction time of 2 h. After polymerization with styrene, the immobilization percentage is 58%, close to the 56% when using non‐KOH‐treated PET.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…). After KOH hydrolysis, the contact angle of PET surface decreases from 85° to 75°, consistent with previous literature . Then the KOH‐treated PET samples were immobilized with styrene using the following conditions: a monomer‐to‐initiator molar ratio of 466, temperature of 100 °C and reaction time of 2 h. After polymerization with styrene, the immobilization percentage is 58%, close to the 56% when using non‐KOH‐treated PET.…”
Section: Resultssupporting
confidence: 87%
“…The effect of the hydrophilicity of PET surface was studied. Using a standard procedure, the PET samples were treated with potassium hydroxide (KOH) solution (1 mol L −1 ) at 85 °C for 90 min in order to partially hydrolyse the ester groups in the PET chains into hydroxyl and carboxyl groups (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acids are barely used for functionalization of activated bromides since the nucleophilicity of carboxylates is relatively weak. For example, nucleophilic substitutions between activated bromides and acids in the presence of potassium fluoride are reported, but high temperature and prolonged reaction time are basically required. Indeed, the esterification efficiency is far from satisfactory if common bases are selected as catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…The transport properties of biomolecules through nanopores depend on interactions of analytes with the nanopore’s surface. , Several reports have discussed the functionalization of pore surfaces to facilitate transport or other properties. For example, Martin et al reported a method to alter the surface properties of track-etched nanopores in polycarbonate with gold by electroless deposition followed by chemisorption of thiols. , For polyimide (PI) and polyethylene terephthalate (PET), the surface carboxyl groups created during track etching were chemically functionalized with an alkyl bromide and KF catalyst, methylation, or amidation. , Previously, our group reported surface modification of PMMA nanochannels to generate both negatively charged and positively charged surfaces . A negatively charged surface was generated via O 2 plasma treatment, which forms carboxyl groups on the thermoplastic surface.…”
mentioning
confidence: 99%